Report on “Polar Data Forum II and related meetings” - Masaki Kanao; Hironori Yabuki; Takeshi Sugimura (Antarctic Record, 2016)
The Second Polar Data Forum (＂Polar Data ForumⅡ＂) was held on October 27-29, 2015 in Waterloo, Ontario, Canada to build on the successes of the first Polar Data Forum held in October 2013 in Tokyo, Japan. Polar Data Forum Ⅱ further refined the themes and priorities regarding polar data management and accelerated progress by establishing clear actions to address the target issues, including meeting the needs of society and science through the promotion of open access data and effective data stewardship, establishing the sharing and interoperability of data at various levels, developing reliable data management systems, and ensuring the long-term preservation of data. The forum was attended by 109 participants from 15 countries, in conjunction with the scheduled annual meetings of the Arctic Data Committee (ADC) of the International Arctic Science Committee (IASC) and the Standing Committee on Antarctic Data Management (SC-ADM) of the Scientific Committee on Antarctic Research (SCAR). Polar Data Forum Ⅱ, together with SC-ADM and ADC annual meetings, proved to be important for showcasing polar data initiatives, for learning from global partners, and working collaboratively to continue developing an international vision and action plan.